Analisis Tindak Tutur Direktif Dalam Film “Nanti Kita Cerita Tentang Hari Ini” - Sherly Anggreni Hasari Br Ginting; Achmad Yuhdi (International Forum of Researchers and Lecturers, 2023)
The purpose of this research is to describe the forms and functions of directive speech acts contained in the film